Prognostic role of plasma level of angiopoietin-1, angiopoietin-2, and vascular endothelial growth factor in hepatocellular carcinoma - Choi, Gwang Hyeon; Jang, Eun Sun; Kim, Jin-Wook; Jeong, Sook-Hyang (World journal of gastroenterology : WJG, 2021)
Most hepatocellular carcinomas (HCCs) are hypervascular, with characteristic features of hepatic arterial supply to the tumor. The factors involved in tumor angiogenesis include angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), and vascular endothelial growth factor (VEGF). To investigate the profiles of plasma levels of angiogenesis markers in patients with HCC and evaluate their roles in predicting overall survival (OS) and progression-free survival (PFS). Plasma samples from 240 prospectively enrolled HCC patients in the very early to advanced stages were used to measure the levels of Ang-1, Ang-2, and VEGF. Their associations with clinical characteristics, OS, and PFS were analyzed. The median plasma levels of Ang-1, Ang-2, and VEGF were 3216 pg/mL, 1684 pg/mL, and 26.5 pg/mL, respectively. The plasma level of Ang-2 showed a significant increase from early stage [Barcelona clinic liver cancer (BCLC) A] to intermediate (BCLC B) and advanced stage HCC (BCLC C/D), whereas Ang-1, VEGF, and alpha-fetoprotein (AFP) levels in the plasma did not show any such changes. Multivariable analysis, propensity score-matched analysis, and time-dependent receiver operating curve analysis revealed that Ang-2 levels had the highest predictive power for OS and PFS. Neither Ang-1 nor VEGF was significantly associated with OS or PFS. The neutrophil-to-lymphocyte ratio was an independent factor for OS and PFS. The plasma levels of Ang-2 correlated with liver function, tumor stage, and tumor invasiveness, showing better performance in predicting OS and PFS than AFP, Ang-1, or VEGF.